2022
DOI: 10.1038/s41598-022-17566-5
|View full text |Cite
|
Sign up to set email alerts
|

A multi modal approach to microstructure evolution and mechanical response of additive friction stir deposited AZ31B Mg alloy

Abstract: Current work explored solid-state additive manufacturing of AZ31B-Mg alloy using additive friction stir deposition. Samples with relative densities ≥ 99.4% were additively produced. Spatial and temporal evolution of temperature during additive friction stir deposition was predicted using multi-layer computational process model. Microstructural evolution in the additively fabricated samples was examined using electron back scatter diffraction and high-resolution transmission electron microscopy. Mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Similar reduction in properties was reported in the case of AZ31B Mg alloy [104] and subsequent efforts by separate set of authors [105,106] examined the reasons behind such a reduction. It was reported that deposition of a single layer can result in deposition of a refined grain material as a result of dynamic recrystallization.…”
Section: Additive Friction Stir Depositionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar reduction in properties was reported in the case of AZ31B Mg alloy [104] and subsequent efforts by separate set of authors [105,106] examined the reasons behind such a reduction. It was reported that deposition of a single layer can result in deposition of a refined grain material as a result of dynamic recrystallization.…”
Section: Additive Friction Stir Depositionsupporting
confidence: 67%
“…Fig 29. Spatial and temporal variation during additive friction stir deposition of AZ31B Mg alloy plotted in a and b for two different processing conditions[106] …”
mentioning
confidence: 99%
“…Yoder et al (Yoder et al, 2021), compared the properties of as-built AA 7075 with the as-wrought feedstock. Joshi et al (Joshi et al, 2022) investigated AFSD of AZ31B and Williams et al (Williams et al, 2021) tested WE43 Mg alloy and obtained a refined, homogenous equiaxed microstructure when compared to the feedstock resulting in a reduction in average grain size from 45 to 2.7 µm on the top layer and 4.5 µm on the bottom one. Griffith et al (Griffiths et al, 2022) tested the feasibility of AFSD of stainless steel 304 under water and showed good deposition quality and remarkable microstructure differences from conventional deposition.…”
Section: Meld L3 Machine Tool Installed In the University Of Kentuckymentioning
confidence: 99%
“…The deposition of parts made of other metal alloys is also reported in the literature. Various aspects of AFSD-fabricated parts made with Titanium alloy [26,42], magnesium alloy [2,[43][44][45], Inconel alloy [46,47], stainless steel [48][49][50], copper alloy [51], and also high-entropy alloy (HEA) [52] are studied in the literature.…”
Section: Introductionmentioning
confidence: 99%